2007
DOI: 10.1529/biophysj.107.107474
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Magnetotactic Bacteria in a Rotating Magnetic Field

Abstract: The dynamics of the motile magnetotactic bacterium Magnetospirillum gryphiswaldense in a rotating magnetic field is investigated experimentally and analyzed by a theoretical model. These elongated bacteria are propelled by single flagella at each bacterial end and contain a magnetic filament formed by a linear assembly of approximately 40 ferromagnetic nanoparticles. The movements of the bacteria in suspension are analyzed by consideration of the orientation of their magnetic dipoles in the field, the hydrodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
107
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 37 publications
7
107
0
Order By: Relevance
“…As has been shown for other polarly flagellated bacteria 37,38 , M. gryphiswaldense does not tumble between smooth swimming phases, but instead swims in a typical run and reversal pattern, with speeds between 20 and 65 mm s À 1 , similar to previously reported values 12,13,39 . In equilibrium conditions, cells showed a reversal frequency of 0.126 s À 1 or less, which is low compared with data reported for non-MTB [40][41][42][43] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As has been shown for other polarly flagellated bacteria 37,38 , M. gryphiswaldense does not tumble between smooth swimming phases, but instead swims in a typical run and reversal pattern, with speeds between 20 and 65 mm s À 1 , similar to previously reported values 12,13,39 . In equilibrium conditions, cells showed a reversal frequency of 0.126 s À 1 or less, which is low compared with data reported for non-MTB [40][41][42][43] .…”
Section: Discussionsupporting
confidence: 89%
“…M. gryphiswaldense has been widely used as a model in many recent studies on magnetosome biosynthesis 11 . However, there has been little investigation of its motility and taxis 8,12,13 , and it is currently not known whether or how the magnetic behaviour of M. gryphiswaldense and other MTB is integrated with other sensory responses at the behavioural and molecular level, or whether it uses a dedicated sensing and signalling machinery.…”
mentioning
confidence: 99%
“…Despite the differences in the ferromagnetic and paramagnetic moments, the two-dimensional rotating magnetic field setup renders similar mathematical structures in the equation of motion in these different cases. Under a rotating magnetic field, a ferromagnetic microswimmer hence also displays synchronous and asynchronous behaviors similar to a paramagnetic microswimmer [29,30]. Finally, it may be biologically relevant to investigate the effects of the run and tumble motility of bacterial cells on the transition from anisotropic to isotropic diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Other related studies to the present work are: The theoretical and experimental study on the dynamics of a microswimmer with a L−shape made by Kummel et al [8], the dynamics of living active particles with a permanent magnetic moment (magnetotactic bacteria) in a rotating field treated by Cebers and coworkers [28,29], and the diffusive behavior of magnetotactic bacteria due to the random switching of the microorganisms flagellar motors reported in [30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Greenberg reported 'ping-pong' movements associated with magnetotactic multicellular organisms (Greenberg et al, 2005). Erglis et al (2007) also observed a 'back and forth' motion when studying the dynamics of Magnetospirillum gryphiswaldense in a rotating uniform magnetic field. An early study by Spormann and Wolfe (1984) called a observed reversal behavior 'tactile behavior,' and they demonstrated the maintenance of a band of cells while aligning the cells with a magnet.…”
Section: Discussionmentioning
confidence: 99%